The regional city: : planning for the end of sprawl - Peter Calthorpe , William Fulton (Island Press, 2001)
In a large conference room in downtown Salt Lake City overlooking the city that Brigham Young laid out some 153 years ago, civic leaders gather to begin the process of envisioning the future of their fast-growing region. The city that was once a precursor to the American dreamâ€”each home on a one-acre lot bounded by streets wide enough for a U-turn by a horse and carriageâ€”has evolved into blocks of parking lots, scattered mid-rise buildings, and sixlane streets recently punctuated with a new light-rail line. The 150 participants sit at small tables in groups of 10, armed with detailed maps of the region and seventy â€œchipsâ€â€”small squares of paper, each representing four square miles of typical suburban growth. Their assignment: to accommodate the next million people in Salt Lake City by finding the best way to arrange the chips on the map. At one of the tables, Utah Governor Mike Leavitt joins a random group that includes the head of a local environmental group, a major housing developer, a small-city mayor, and other community representatives. First, they lay the chips side by side in classic suburban fashion. But soon the chips have covered almost all of the regionâ€™s dwindling agricultural land. Then they look for other buildable pieces of land and begin laying the chips on pristine mountain plateaus, accessible to Salt Lake City only through scenic mountain passes. The participants at the governorâ€™s tableâ€”and throughout the roomâ€”soon realize that if the Salt Lake region continues to grow at the current densities, much of what they love about the Wasatch Front will be destroyed. So each group takes a different approach. Instead of spreading the chips out, the participants begin stacking them, one on top of the otherâ€”indicating that they are willing to accept higher densities in order to preserve agriculture and pristine land. When that isnâ€™t enough, they begin laying the chips on top of existing urban areasâ€”in places that they know are underbuilt or in need of renewal. By the time they are done, they recognize that a different vision of their future is necessary and possible.